Kinetics and selectivity of methane oxidation on an IrO2(110) film. (13th July 2022) - Lee, Christopher J; Vashishtha, Saumye; Shariff, Mohammed; Zou, Fangrong; Shi, Junjie; Meyer, Randall J; Weaver, Jason F
Abstract: Undercoordinated, bridging O-atoms (Obr ) are highly active as H-acceptors in alkane dehydrogenation on IrO2 (110) surfaces but transform to HObr groups that are inactive toward hydrocarbons. The low C–H activity and high stability of the HObr groups cause the kinetics and product selectivity during CH4 oxidation on IrO2 (110) to depend sensitively on the availability of Obr atoms prior to the onset of product desorption. From temperature programmed reaction spectroscopy (TPRS) and kinetic simulations, we identified two Obr -coverage regimes that distinguish the kinetics and product formation during CH4 oxidation on IrO2 (110). Under excess Obr conditions, when the initial Obr coverage is greater than that needed to oxidize all the CH4 to CO2 and HObr groups, complete CH4 oxidation is dominant and produces CO2 in a single TPRS peak between 450 and 500 K. However, under Obr -limited conditions, nearly all the initial Obr atoms are deactivated by conversion to HObr or abstracted after only a fraction of the initially adsorbed CH4 oxidizes to CO2 and CO below 500 K. Thereafter, some of the excess CH x groups abstract H and desorb as CH4 above ∼500 K while the remainder oxidize to CO2 and CO at a rate that is controlled by the rate at which Obr atoms are regenerated from HObr during the formation of CH4 and H2 O products. We also show that chemisorbed O-atoms ('on-top O') on IrO2 (110) enhance CO2 production below 500 K by efficiently abstracting H from Obr atoms and thereby increasing the coverage of Obr atoms available to completely oxidize CH x groups at low temperature. Our results provide new insights for understanding factors which govern the kinetics and selectivity during CH4 oxidation on IrO2 (110) surfaces.